Islam dan Konservasi Sumber Daya Alam - Minarno, Eko Budi (el Harakah: Jurnal Budaya Islam, 1999)
Among the various crises, worrying enough is the start of the scarcity of some Natural Resources (SDA), especially from unrecoverable groups such as petroleum, metals and minerals. And by often ignoring the needs of other living beings as well as the needs of future generations. If then comes a crisis with respect to this SDA, which is affected negatively human finally. SDA is needed by humans in the past, present and future. The threat to the existence and sustainability of natural resources is just the same as the threat to human existence and survival. The conservation of natural resources, which is essentially the management of natural resources, is an absolute must and is the main responsibility of human being as the Caliph of this earth. There are three main tasks for human beings related to the conservation of natural resources including al Intifa '(nurture and utilize), al I'tibar (think, be grateful, explore the secrets of nature), and al Islah (preserve and deliberate sustainability for the benefit of people, and the creation of harmony of life nature of Allah's creation. Di antara berbagai krisis, yang cukup mengkhawatirkan adalah mulai terjadinya kelangkaan beberapa Sumber Daya Alam (SDA) terutama dari kelompok yang tidak terpulihkan seperti minyak bumi, logam, dan mineral. Dan dengan sering mengabaikan kebutuhan makhluk hidup yang lain maupun kebutuhan generasi yang akan datang. Kalau kemudian muncul krisis sehubungan dengan SDA ini, yang terkena darnpak negatif akhirnya manusia juga. SDA sangat dibutuhkan oleh manusia dimasa lalu, sekarang dan yang akan datang. Ancaman terhadap keberadaan dan kelangsungan SDA sama saja artinya dengan ancaman terhadap keberadaan dan kelangsungan hidup manusia. Konservasi SDA yang berintikan pengelolaan SDA, adalah suatu hal yang mutlak harus dilaksanakan dan menjadi tanggung jawab utama manusia sebagai khalifah di bumi ini. Ada tiga tugas utama bagi manusia berkaitan dengan koservasi SDA meliputi al Intifa’ (memelihara dan mendayagunakan), al I’tibar (memikirkan, mensyukuri, menggali rahasia alam), dan al Islah (memelihara dan sengaja kelestarian untuk kemslahatan umat, serta terciptanya harmoni kehidupan alam ciptaan Allah SWT.